2018
DOI: 10.1209/0295-5075/124/18006
|View full text |Cite
|
Sign up to set email alerts
|

High signal/noise ratio deep UV detector with maximum response at 230 nm based on mix-phase MgZnO deposited under high laser energy condition

Abstract: Mix-phase MgZnO thin film was fabricated on the c-plane sapphire substrate (Mg0.4Zn0.6O target) under high laser energy density condition by the PLD method. The internal quantum efficiency of the detector based on the mix-phase MgZnO thin film at 230 nm deep UV light reached 86% at 40 V bias voltage. And the Iuv(230 nm)/I dark ratio of the MgZnO detector reached 864 at 40 V bias voltage, which is mainly caused by both the higher internal gain of the detector at deep UV light and its smaller I dark . The high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To maintain the equilibrium of the mixed-phase interface Fermi level, the electrons in the crystalline Ga 2 O 3 will migrate to the amorphous Ga 2 O 3 , thereby inducing the energy levels near the amorphous Ga 2 O 3 bending upwards to form a built-in electric field (space charge region) around the interface. When two parts finally reach the same E f , the built-in electric field from the crystalline phase to the amorphous one will prevent the further diffusion of charges [10,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To maintain the equilibrium of the mixed-phase interface Fermi level, the electrons in the crystalline Ga 2 O 3 will migrate to the amorphous Ga 2 O 3 , thereby inducing the energy levels near the amorphous Ga 2 O 3 bending upwards to form a built-in electric field (space charge region) around the interface. When two parts finally reach the same E f , the built-in electric field from the crystalline phase to the amorphous one will prevent the further diffusion of charges [10,28].…”
Section: Resultsmentioning
confidence: 99%
“…Ga 2 O 3 is a natural n-type oxide semiconductor material [2,3,70]. According to the traditional theory of n-n heterojunction, the bias voltage applied to wide bandgap semiconductor is predominantly concentrated at the interface between different phase parts [28]. Since the crystalline and amorphous domains of mixedphase Ga 2 O 3 are considerably small, V 1 and V 2 are, respectively, approximated as the voltage applied to the interface between crystalline and amorphous domains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] To overcome the above-mentioned issue, it is essential to use ultra-wide band gap (UWBG, bandgap over 3.4 eV) materials as photoactive substances beyond wide band gap (WBG, bandgap exceeds 3.1 eV) materials. In the past decades, various studies have reported DUV PDs using UWBG materials such as Ga 2 O 3 , [17][18][19] Mg x Zn 1-x O, [20][21][22] Al 1-x Sn x O, [23] III-nitrides (Al x Ga 1-x N, [24][25][26] AlN, [27][28][29] and BN [30][31][32] ), and diamond. [33][34][35] The high crystalline UWBG semiconductors provide the narrowband photo response based on bulk charge generation through the incident wavelength near optical bandgap.…”
Section: Introductionmentioning
confidence: 99%